Mutual health insurance and its contribution to improving child health in Rwanda - Agnes Binagwaho; Renate Hartwig; Denyse Ingeri; Andrew Makaka (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2012)
Rwanda is among the few countries in Sub-Saharan Africa and the developing approaching universal health insurance coverage. To date, over 90 per cent of the population are enrolled in the Mutuelles de Santé - a system that started off from a number of stand-alone community based health insurance schemes and gradually evolved into a unified social health insurance plan. The country has also made remarkable progress in ameliorating child health, particularly since 2005, which coincides with the year when the Mutuelles de Santé was standardised and raises the question to what extent the insurance scheme did contribute to the observed improvements. In order to address this issue we conduct a quantitative impact evaluation using nationally representative micro-data from the 2005 and 2010 Rwandan Demographic and Health Surveys (RDHSs) and also consider potential channels from which improvements could originate. Our results suggest the following: The Mutuelles de Santé improves access to preventative and curative health services. Insured households are more sensitive to health issues, in the sense that they are more inclined to use bed nets and ensure safe drinking water. Despite a weak effect on health outcomes overall, the insurance scheme seems to have contributed to improvements in stunting and mortality, at the critical ages (before the age of two).
Keywords: I11; I38; J13; 330; Health Insurance; Child Health; Mutuelles de Santé; Rwanda; Krankenversicherung; Gesetzliche Krankenversicherung; Wirkungsanalyse; Kinder; Gesundheit; Ruanda